Use of cellulose filters to isolate Campylobacter spp. from naturally contaminated retail broiler meat - Speegle, Leslie; Miller, Michael E.; Backert, Steffen; Oyarzabal, Omar A. (Journal of Food Protection, 2009)
Membrane filtration has been used to isolate Campylobacter spp. from feces, although ∼5 log CFU/g must be present in the sample. Few studies have attempted to use filter membranes for the isolation of Campylobacter from foods. We investigated the minimum number of thermotolerant Campylobacter cells that pass through cellulose filters, the effect of different cell conditions on the rate of passage, and the minimum number of cells that could pass the filters from enriched broiler meat naturally contaminated with Campylobacter spp. Cellulose filters with 0.65-μm pore sizes retained fewer cells and were more effective than filters with 0.45-μm pore sizes. Scanning electron microscopy revealed that 15 min of contact of the filters with agar plates allowed for the passage of most bacteria. The minimum number of bacteria required to pass through the filters was contingent on cell conditions; nonmotile cells were retained more than motile cells (P < 0.05). The minimum number of motile bacteria from 24-h cultures and centrifuged cells were 2.2 and 2.1 log CFU, respectively, while the number of coccoid and nonmotile (flaAIB∼ mutant) cells were 4.1 and 3.4 log CFU, respectively. Broiler meat samples enriched in Bolton's broth supplemented with 5% lysed blood showed that approximately 1.7 log CFU of Campylobacter can be filtered to pure colonies on agar plates. These results demonstrate that the motility of the bacteria influences passage through cellulose filters and that 0.65-μm-pore-size filters on agar plates help obtain pure Campylobacter colonies from enriched food samples. Copyright © International Association for Food Protection.
Created from Fastlane, Scopus look-up